Design And Implementation Of 256 Bit Advanced Encryption Standard On FPGA - Prof. Nilesh A.Mohota, Pallavi A. Vaidya, (International Journal of Scientific Research and Management (IJSRM), 2015)
his paper presents architecture of the Advanced Encryption Standard (AES-Rijndael) cryptosystem. The reconfigurable architecture is capable of handling all possible combinations of standard bit lengths (128,192,256) of data and key. The two main parts of AES algorithm, namely encryption and key expansion, are considered for optimization. The major optimization criteria considered are maximization of hardware reduction and path delay reduction. The fully rolled inner-pipelined architecture ensures lesser hardware complexity. A new AES algorithm with 256-bit keys (AES-256) was described in this paper, which is to be realized in Verilog Hardware Description Language on FPGA board. In this novel work, substantial improvement in performance in terms of area, power and dynamic speed is obtained.   This gives low complexity architecture and will easily achieve low latency as well as high throughput